2013
DOI: 10.3109/07420528.2012.763042
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Chronotype Questionnaire Including an Amplitude Dimension

Abstract: The aim of this paper was to validate a French version of the Chronotype Questionnaire (Ogińska, 2011, Pers. Individ. Dif. 50:1039-1043), which represents an interesting novelty in the psychometric assessment of chronotype, because it comprises not only an assessment of the morningness-eveningness (ME) dimension, but also a distinctness (DI) dimension (i.e., amplitude), which represents the range of diurnal variation. In study 1, we aimed to confirm the structure of the Chronotype Questionnaire, with two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 42 publications
(77 reference statements)
4
35
1
Order By: Relevance
“…The protocol and the consent form were fully approved by the review board "Local committee of the Laboratory of Biochemistry, CHU Habib Bourguiba, Sfax, Tunisia" before the commencement of the assessments. Answers to the Dosseville et al (13), the questionnaire categorized the subjects as "moderately morning type" (n = 1) or "neither type" (n = 8).…”
Section: Participantsmentioning
confidence: 99%
“…The protocol and the consent form were fully approved by the review board "Local committee of the Laboratory of Biochemistry, CHU Habib Bourguiba, Sfax, Tunisia" before the commencement of the assessments. Answers to the Dosseville et al (13), the questionnaire categorized the subjects as "moderately morning type" (n = 1) or "neither type" (n = 8).…”
Section: Participantsmentioning
confidence: 99%
“…However, further research is needed for clarifying relationships of the particular subscales (tetrads) of this new tool with the earlier proposed subconstructs of the sleep-wake adaptability, such as rigidity/flexibility and languidness/vigorousness (Di Milia et al, 2005), time awareness and strength of the early/ late preference (Di Milia et al, 2011), and distinctness of the diurnal rhythm of activation (Dosseville et al, 2013;Ogińska, 2011). Additional research efforts are also required for further improvement of the content of the new inventory.…”
Section: Discussionmentioning
confidence: 94%
“…Instead, DiMilia and Folkard (2009) more recently identified two other additional to early/late preference dimensions that can be self-assessed with the scales of the time awareness and strength of the early/late preference (Di Milia et al, 2011). Moreover, one of more recent proposals was to construct two-scale questionnaire tool that includes an amplitude scale for assessing distinctness (strong versus weak) of the diurnal rhythm of activation and a more traditional phase (morningness-eveningness) scale (Dosseville et al, 2013;Ogińska, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Given that some people shows fluctuations throughout the day, while others are more stable in their alertness and mood [53], Ogińska [54] and Dosseville et al [55] proposed the amplitude (the range of diurnal changes in morningness-eveningness) as an additional measure of circadian rhythm. The distinctness (DI) scale was developed to evaluate subjective amplitude, indicating the subjective feeling of distinctness of daily changes [54,55].…”
Section: Morningness-eveningness-stability-scale Improvedmentioning
confidence: 99%
“…The MESSi comprises items of CSM [7], Caen Chronotype Questionnaire [55], and Circadian Energy Scale [56]. Randler et al [10] identified three subscales: 1) MA, 2) eveningness (EV), and 3) DI.…”
Section: Morningness-eveningness-stability-scale Improvedmentioning
confidence: 99%